(untitled) (Bangladesh Rice Journal, 2017)
Cross infection between rice and wheat blast fungi was investigated in a series of experiments conducted under controlled glasshouse condition following a completely randomized design. Two rice (BRRI dhan29 and LTH) and two wheat (BARI Gom25 and BARI Gom26) varieties were grown in plastic trays as sole and rice-wheat mixed crop culture. Plants were artificially inoculated using virulent isolates of rice and wheat blast fungi. It was observed that irrespective of variety and crop culture technique, all the isolates of wheat blast fungus caused significant 100% plant infection on leaf typical leaf blast symptoms appeared on wheat seedlings but no blast symptom on rice. Conversely, the test-isolates of rice blast fungus did not produce any disease reaction on wheat seedlings, though leaf blast was observed on 100% rice plants. Therefore, we conclude that rice blast pathogen population is different from those of wheat blast pathogen (Pyricularia oryzae). Bangladesh Rice j. 2016, 20(2): 21-29